2018
DOI: 10.1007/s00011-018-1165-4
|View full text |Cite
|
Sign up to set email alerts
|

Air particulate matter SRM 1648a primes macrophages to hyperinflammatory response after LPS stimulation

Abstract: ObjectiveExposure to air particulate matter (PM) is associated with chronic inflammatory and autoimmune diseases. Macrophages are responsible for the regulation of chronic inflammation. However, whether PM affects macrophage polarization remains unclear. The aim of this study was to evaluate whether nontoxic concentrations of urban PM are able to prime macrophages to altered inflammatory response upon LPS challenge.MethodsWe used two forms of the urban particulate matter SRM 1648a, intact PM and PM deprived of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
23
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 49 publications
(58 reference statements)
7
23
0
1
Order By: Relevance
“…Effect of TMCPM on the activity of human CD4+ T cell subsets was investigated after five hours of healthy donor PBMCs exposure to NIST or LAP particles. The concentrations of NIST and LAP used in the study were established experimentally in a range from 1-100 μg/mL, as used at higher concentrations were cytotoxic (data not shown), confirming previous reports [22]. At first, we checked weather TMCPM may affect the proportion of CD4+ T cells and the expression of CD4 on their surface, as was documented for PMA and ionomycin [25][26][27], potent activators of T cells.…”
Section: Tmcpm Reduces the Expression Level Of Cd4 On The Surface Of supporting
confidence: 81%
See 2 more Smart Citations
“…Effect of TMCPM on the activity of human CD4+ T cell subsets was investigated after five hours of healthy donor PBMCs exposure to NIST or LAP particles. The concentrations of NIST and LAP used in the study were established experimentally in a range from 1-100 μg/mL, as used at higher concentrations were cytotoxic (data not shown), confirming previous reports [22]. At first, we checked weather TMCPM may affect the proportion of CD4+ T cells and the expression of CD4 on their surface, as was documented for PMA and ionomycin [25][26][27], potent activators of T cells.…”
Section: Tmcpm Reduces the Expression Level Of Cd4 On The Surface Of supporting
confidence: 81%
“…In keeping, recently Mikrut et al, using the same preparations of TMCPM showed that the organic fraction from NIST was mostly responsible for singlet oxygen photogeneration when compared with LAP particles [23]. In another study, Gawda et al showed that the urban particulate matter SRM 1648a induced in vitro a dose-dependent production of pro-inflammatory cytokines (TNF-α, IL-6, IL-12p40) by murine macrophages [22]. Interestingly, under the same conditions, LAP particles were not able to stimulate macrophages, however the cells primed with NIST or LAP showed a strong pro-inflammatory response upon LPS challenge.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Similar results were found for cytokine expression in the lung. Several pro-inflammatory factors are released from macrophages, such as ILs and TNF-α [13,47]. Previous article suggested that different sizes of particles may through different regulated pathways to affect the alveolar macrophages, such as coarse particles are via endotoxin-toll-like receptor (TLR) 4 pathway; while the fine and ultrafine particles are transition metals and/or polyaromatic hydrocarbons to generate ROS to activate innate immune responses [13].…”
Section: Discussionmentioning
confidence: 99%
“… 1 ; 2 ; 3 ; 4 ; 5 ; 6 ; 7 ; 8 ; 9 ; 10 ; 11 ; 12 ; 13 ; 14 ; 15 ; 16 ; 17 ; 18 ; 19 ; 20 ; 21 ; 22 ; 23 ; 24 ; 25 ; 26 ; 27 ; 28 ; 29 ; 30 ; 31 ; 32 ; 33 ; 34 ; 35 ; 36 ; 37 ; 38 ; 39 ; 40 ; 41 ; 42 ; 43 ; 44 ; 45 ; 46 ; 47 ; 48 ; 49 ; 50 ; 51 ; 52 .…”
Section: Uncited Referencesunclassified